DYNAMIC VISUALIZATION OF THE SPREAD OF COVID-19 IN MEDAN CITY USING HEATMAP WITH PYTHON - Mhd Fikri Hasrul Hasibuan; Fredy Kusuma Ramadhani; Lailatul Badria; Laila Nurzannah; Fikri Haikal; Mhd Furqan (Smart Education, 2025)
Abstract: The rapid and widespread transmission of COVID-19 has posed significant challenges for public health management, particularly in densely populated urban areas like Medan. Manual data reporting often fails to convey the dynamic nature of the virus's spread in a clear and actionable manner. This study aims to address this gap by developing dynamic visualizations of COVID-19 distribution using heat maps created with Python programming. The study utilized official COVID-19 datasets sourced from platforms like Kaggle, which include district- and municipal-level data across North Sumatra. Methodological steps included data collection, preprocessing, and visualization using Python libraries like Pandas and Matplotlib. These tools enable the transformation of static tabular data into interactive heat maps that highlight spatial and temporal trends in infections, recoveries, and mortality. The visualizations reveal that Medan City recorded the highest number of confirmed and recovered cases, while Deli Serdang had the highest number of deaths. Conversely, North Nias and South Nias showed the lowest mortality rates. The resulting spreadsheets provide a practical solution for monitoring the pandemic's development and serve as decision-support tools for policymakers and health authorities. In conclusion, dynamic data visualization improves understanding of COVID-19 patterns and supports effective pandemic response strategies.Keywords: dynamic visualization; COVID-19; python; heatmap.Â Abstrak: Penularan COVID-19 yang cepat dan meluas telah menimbulkan tantangan yang signifikan bagi manajemen kesehatan masyarakat, terutama di daerah perkotaan yang padat penduduk seperti Kota Medan. Laporan data manual sering kali gagal menyampaikan sifat dinamis penyebaran virus dengan cara yang jelas dan dapat ditindaklanjuti. Penelitian ini bertujuan untuk mengatasi kesenjangan ini dengan mengembangkan visualisasi dinamis distribusi COVID-19 menggunakan peta panas yang dibuat dengan pemrograman Python. Penelitian ini menggunakan kumpulan data resmi COVID-19 yang bersumber dari platform seperti Kaggle, yang mencakup data tingkat kabupaten dan kotamadya di seluruh Sumatera Utara. Langkah-langkah metodologis meliputi pengumpulan data, prapemrosesan, dan visualisasi menggunakan pustaka Python seperti Pandas dan Matplotlib. Alat-alat ini memungkinkan transformasi data tabular statis menjadi peta panas interaktif yang menyoroti tren infeksi, pemulihan, dan mortalitas secara spasial dan temporal. Visualisasi tersebut mengungkapkan bahwa Kota Medan mencatat jumlah kasus terkonfirmasi dan sembuh tertinggi, sementara Deli Serdang memiliki jumlah kematian tertinggi. Sebaliknya, Nias Utara dan Nias Selatan menunjukkan tingkat mortalitas terendah. Heatmap yang dihasilkan memberikan solusi praktis untuk memantau perkembangan pandemi dan berfungsi sebagai alat pendukung keputusan bagi para pembuat kebijakan dan otoritas kesehatan. Kesimpulannya, visualisasi data dinamis meningkatkan pemahaman pola COVID-19 dan mendukung strategi respons pandemi yang efektif.Kata Kunci: visualisasi dinamis; COVID-19; python; peta panas.